Opening Ceremony Inviting Inclusion into University Governance - Gindlesparger, Kathryn J. (Forerunners: Ideas First, 2023)
p strongExplores how university governance is restricted by ceremony and what it must do to survive/strong /p pUniversity shared governance is a microcosm of regulation and thrives particularly on ceremony to communicate its relevance. While many investigations of university governance examine representation, emOpening Ceremony/em offers that, instead, stakeholders' belief in institutional values can invite revision of stagnant governance practices. Governance tells us what the rules are, but they also tell us how to feel: opening up the ceremonial communication of this system invites new participants to rewrite how universities respond to felt needs./p pKathryn J. Gindlesparger considers how to break the seal of ceremony to invite voices not traditionally heard in governance and, in doing so, protect the ideals of the institution and rebuild trust in higher education./p